2017
DOI: 10.1002/mbo3.430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hay supplementation timing on rumen microbiota in suckling calves

Abstract: An animal feeding trial was conducted on 18 seven‐day‐old Holstein dairy bull calves weighing 42 ± 3 kg each. Calves were randomly assigned into three groups (n = 6 each). The dietary treatments were as follows: (1) milk and starter for the control group (MS), (2) supplementation of oat hay from week 2 on the basis of milk and starter (MSO2), and (3) supplementation of oat hay from week 6 on the basis of milk and starter (MSO6). All animals were fed starter and oat hay ad libitum. The major phyla in the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This finding suggests that early weaning stress could have a negative effect on rumen development. Bacteroidetes plays a role in the normal development of the digestive tract, affecting traits such as the growth and volume increase of the rumen (Thomas et al, 2011;Lin et al, 2018). Seven genera exhibited significant differences in relative abundance among treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that early weaning stress could have a negative effect on rumen development. Bacteroidetes plays a role in the normal development of the digestive tract, affecting traits such as the growth and volume increase of the rumen (Thomas et al, 2011;Lin et al, 2018). Seven genera exhibited significant differences in relative abundance among treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be speculated that forage inclusion in the diet might affect the growth of lactic acid-producing bacteria (such as Olsenella) by limiting the proportion of rapidly fermentable substrates (e.g., starch) replaced by fiber. In contrast, although numerical differences were observed in Bacteroidetes and Actinobacteria when evaluating the effect of forage supplementation, Lin et al [108] reported that neither alpha nor beta diversity indices and microbiota were significantly different among the dietary groups [108], possibly because of the volume of milk (Lin, 252 L, 10% vs. Kim, 88 L, 4% of birth bodyweight) fed to calves, resulting in varying solid feed consumed. Alternatively, different forage sources (Lin, Oat hay vs. Kim, Timothy) and feeding levels (Forage/Total Solid: Lin, 6% vs. Kim, 20%) (Tables 2 and 4) might have led to insufficient forage consumption causing the changes in the composition of rumen microbiota in the Lin et al study.…”
Section: Rumen Microbesmentioning
confidence: 98%
“…The next-generation sequencing (NGS) analysis has revealed that the major phyla in the rumen are Firmicutes (around 43%), Bacteroidetes (around 21%), Actinobacteria (around 18%), and Proteobacteria (around 4%) [108]. Relatively higher abundance of Bacteroidetes and lower abundance of Actinobacteria was observed in calves supplemented with forage compared to those fed only concentrate [54].…”
Section: Rumen Microbesmentioning
confidence: 99%
“…Although rumen microorganisms are relatively stable, they are highly responsive to changes in host genetics (Huang et al, 2017), feeding paradigms (Xue et al, 2017) and diet (Lin et al, 2018;Liu et al, 2019), age (Jami et al, 2013) and environmental factors (Uyeno et al, 2010). Of these, diet was the key factor in determining microbial community structure (Tajima et al, 2001).…”
Section: Major Factors Determining Rumen Microbial Diversitymentioning
confidence: 99%